2004
DOI: 10.1109/tmag.2004.825319
|View full text |Cite
|
Sign up to set email alerts
|

Real Coded Genetic Algorithm for Jiles–Atherton Model Parameters Identification

Abstract: Abstract-The parameters set of the Jiles-Atherton hysteresis model is identified by using a real coded genetic algorithm. The parameters identification is performed by minimizing the mean squared error between experimental and simulated magnetic field curves. The procedure is validated by comparing experimental and simulated results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 10 publications
0
49
0
Order By: Relevance
“…However, when applying the model, five key parameters need be determined by fitting based on test data with a complex mathematical method. Leite et al [34] used a genetic algorithm to determine the five parameters and verified them using the least mean square error between the experimental and simulated results. Jaafar [35] studied the influence of the five parameters on the magnetization process and found that each parameter significantly impacts the prediction accuracy of the magnetization and hysteresis mathematical models.…”
Section: -Magnetization Curvementioning
confidence: 99%
“…However, when applying the model, five key parameters need be determined by fitting based on test data with a complex mathematical method. Leite et al [34] used a genetic algorithm to determine the five parameters and verified them using the least mean square error between the experimental and simulated results. Jaafar [35] studied the influence of the five parameters on the magnetization process and found that each parameter significantly impacts the prediction accuracy of the magnetization and hysteresis mathematical models.…”
Section: -Magnetization Curvementioning
confidence: 99%
“…The optimal values of seven parameters and are estimated using the DE algorithm. Past studies have presented a number of optimal algorithms, such as the genetic algorithm (GA) [10], [11]; neural networks [12]; particle swarm optimization (PSO) [13] , etc. However, in cases of transformer internal fault identification, GA often has difficulties finding the global minimum due to premature convergence [10] and, moreover, iteration and calculation time of GA are more than DE.…”
Section: Optimization Methodsmentioning
confidence: 99%
“…Nowadays GA is considered a bit of an outdated technique (originally proposed by Holland in 1975), in most cases it has been successfully superseded by the more recent and effective differential evolution. Genetic algorithms, either in the binary or floating number representation, have been successfully applied for the task of recovery of optimal values of JA model parameters in the papers [1,[15][16][17][18][19].…”
Section: Comparison Of Different Estimation Techniquesmentioning
confidence: 99%